Macrophage Migration Inhibitory Factor as a Novel Biomarker of Portopulmonary Hypertension. (1st December 2016) - DuBrock, Hilary M.; Rodriguez‐Lopez, Josanna M.; LeVarge, Barbara L.; Curry, Michael P.; VanderLaan, Paul A.; Zsengeller, Zsuzsanna K.; Pernicone, Elizabeth; Preston, Ioana R.; Yu, Paul B.; Nikolic, Ivana; Xu, Dihua; Thadhani, Ravi I.; et al.
Abstract : Portopulmonary hypertension (POPH) is a poorly understood complication of liver disease associated with significant morbidity and mortality. We sought to identify novel biomarkers of POPH disease presence and severity. We performed a prospective, multicenter, case‐control study involving patients with liver disease undergoing right heart catheterization. POPH cases were defined as a mean pulmonary arterial pressure (mPAP) ≥25 mmHg and pulmonary vascular resistance (PVR) >240 dynes·s·cm −5 . Plasma samples were collected from the systemic and pulmonary circulation, and antibody microarray was used to identify biomarkers. Characterization and validation of a candidate cytokine, macrophage migration inhibitory factor (MIF), was performed using enzyme‐linked immunosorbent assay. Continuous variables were compared using a Mann‐Whitney U test and correlated with disease severity using Spearman correlation. MIF levels were elevated in both the systemic and pulmonary circulation in patients with POPH compared with controls (median MIF level [interquartile range] in systemic circulation: 46.68 ng/mL [32.31–76.04] vs. 31.19 ng/mL [26.92–42.17], P = 0.009; in pulmonary circulation: 49.59 ng/mL [35.90–108.80] vs. 37.78 [21.78–45.53], P = 0.002). In patients with POPH, MIF levels were positively correlated with PVR ( r = 0.58, P = 0.006) and inversely correlated with cardiac output ( r = −0.57, P = 0.007). MIF >60 ng/mL or tricuspid regurgitation gradient >50 mmHg had a 92% sensitivity and specificity for the diagnosis of POPH, with a positive predictive value of 86% and a negative predictive value of 96%. MIF is a promising novel biomarker of POPH disease presence and severity in patients with liver disease and portal hypertension.